2011
DOI: 10.1007/s10661-010-1869-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic damage induced by lead chloride in different tissues of fresh water climbing perch Anabas testudineus (Bloch)

Abstract: The present investigation was undertaken to study the induction of DNA damage by lead chloride (PbCl(2)) in freshwater climbing perch Anabas testudineus using alkaline single cell gel electrophoresis (comet assay). Based on the LC(50) values of lead chloride of A. testudineus three different concentrations viz., 0.1, 1.0 and 2.0 mg/L were selected to expose fish. The DNA damage was observed in the gill, kidney and liver tissue as the percentage of DNA in comet tails and comet heads in the tissue of the exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…2). The current results are in agreement with the previous research revealing damage to DNA in terms of tail length in gills and liver due to heavy metals pollution overload in different fish species like B. barbus 55,56 , A. testudineus 57 , and mullet and sea bass 58 . It has been reported that when ROS production surpasses the fish defense system due to excessive overload of heavy metals/xenobiotics and comes in contact with DNA and form adducts, it ultimately leads to cellular lesions or DNA damage 6,59 .…”
Section: Genotoxicitysupporting
confidence: 93%
“…2). The current results are in agreement with the previous research revealing damage to DNA in terms of tail length in gills and liver due to heavy metals pollution overload in different fish species like B. barbus 55,56 , A. testudineus 57 , and mullet and sea bass 58 . It has been reported that when ROS production surpasses the fish defense system due to excessive overload of heavy metals/xenobiotics and comes in contact with DNA and form adducts, it ultimately leads to cellular lesions or DNA damage 6,59 .…”
Section: Genotoxicitysupporting
confidence: 93%
“…Besides zebrafish as the fish model that lives in a freshwater environment, several other predominantly freshwater as well as brackish water species are used for the assessment of different contaminants using the comet assay; they include brown trout (Salmo trutta fario) [85], marble trout (Salmo marmoratus) [124], trout (Salmo cenerinus) [124], rainbow trout (Oncorhynchus mykiss) [125,126], common carp (Cyprinus carpio) [76, 82,127], major carp (Catla catla) [128], mrigal carp (Cirrhinus mrigala) [128], gibel carp (Carassius auratus gibelio) [129], common barbell (Barbus barbus) [130], common bleak (Alburnus alburnus) [131,132], freshwater bream (Abramis brama) [133], silver bream (Abramis bjoerkna) [134], white-eye bream (Abramis sapa) [134], rohu (Labeo rohita) [135][136][137][138][139], orangefin labeo (Labeo calbasu) [86], brown bullhead (Ameiurus nebulosus) [76,140], chub (Leuciscus cephalus) [141][142][143], European chub (Squalius cephalus) [87,[144][145][146], pale chub (Zacco platypus) [147], climbing perch (Anabas testudineus) [148], small-scaled pacu (Piaractus mesopotamicus) [149,150], eastern mosquitofish (Gambusia holbrooki) [77], Nile tilapia (Oreochromis niloticus) [151][152][153]…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Similarly to our data, maximal increase reached approximately a 2.7-fold increase as compared to controls and no differences were observed between the exposure time periods. More recently, in the freshwater fish Prochilodus lineatus treated with 5 mg/L lead nitrate for 6 to 96 h, Monteiro et al (2011) reported that while the comet assay showed a genotoxic effect in blood, gill, and liver cells only after 96 h, MNi frequency did not increase at any exposures; nonetheless, the frequency of other erythrocyte nuclear abnormalities showed a significant increase after 24 and 96 h. Likewise, by means of the comet assay, concentration-dependent DNA damage was shown in the gills, kidney, and liver of freshwater climbing perch Anabas testudineus exposed to 0.1-2 mg/L lead chloride for 96 h (Ahmed et al 2011b).…”
Section: Discussionmentioning
confidence: 87%
“…The MN test can be carried out in any proliferating active tissue. The blood, gill, liver, kidney, and fin cells have been mainly used (Al-Sabti and Metcalfe 1995;Cavas et al 2005;Udroiu 2006;Cavaş 2008;Ahmed et al 2011b). However, peripheral erythrocytes are the most commonly employed cells in the piscine MN test because it avoids the complex cellular dissociation required in other tissues, which may lead to mechanical stress and cell damage, as well as the killing of the animals (Bolognesi et al 2006;Cavaş 2008).…”
Section: Introductionmentioning
confidence: 99%